Hypogammaglobulinemia in Adolescents and Young Adults with Acute Lymphoblastic Leukemia - Lange, Cassandra S. (J Adolesc Young Adult Oncol, 2020)
Hypogammaglobulinemia is a poorly described complication of chemotherapy in adolescents and young adults (AYAs, 15–39 years) with acute lymphoblastic leukemia (ALL). The majority of AYAs treated on a Berlin–Frankfurt–Munster-based ALL regimen experienced hypogammaglobulinemia (65.0% [13/20]). Febrile neutropenia episodes (throughout the treatment course) and infectious events during maintenance occurred more frequently in hypogammaglobulinemic patients compared with patients with normal immunoglobulin G levels (n = 7) (median 1.0 vs. 0.0, p = 0.02; 7.0 vs. 3.0, p = 0.02, respectively). Hypogammaglobulinemia did not impact overall or event-free survival. Further studies are needed to elucidate the etiology of hypogammaglobulinemia and to establish criteria for immunoglobulin replacement in these patients.